Russian verbal affixes and aspectual underspecification - Batiukova, Olga (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper presents a treatment of aspectual formation in Russian based on the eventive characteristics of verbal forms. Unlike other proposals of this kind, my hypothesis assumes that aspect-changing processes in this language transform the event structure of the verb in two different ways: the perfectivizing prefixation selects for certain parts of the simple event as well as adds some extra bits of idiosyncratic meaning related to the manner of action (intensity, attenuation, adversity, etc.); the imperfectivizing suffixation, in turn, is in charge of multiplying events or visualizing their preparatory phase. Thus, it is also confirmed that the mentioned processes are applied at different levels: the former is basically lexical and the letter syntactic. Concrete examples of the event structure transformations throughout the aspectual derivation are given.